Haematological analysis of Japanese macaques (Macaca fuscata) in the area affected by the Fukushima Daiichi Nuclear Power Plant accident. Issue 1 (December 2018) - Urushihara, Yusuke; Suzuki, Toshihiko; Shimizu, Yoshinaka; Ohtaki, Megu; Kuwahara, Yoshikazu; Suzuki, Masatoshi; Uno, Takeharu; Fujita, Shiori; Saito, Akira; Yamashiro, Hideaki; Kino, Yasushi; Sekine, Tsutomu; et al.
Abstract Several populations of wild Japanese macaques (Macaca fuscata ) inhabit the area around Fukushima Daiichi Nuclear Power Plant (FNPP). To measure and control the size of these populations, macaques are captured annually. Between May 2013 and December 2014, we performed a haematological analysis of Japanese macaques captured within a 40-km radius of FNPP, the location of a nuclear disaster two years post-accident. The dose-rate of radiocaesium was estimated using the ERICA Tool. The median internal dose-rate was 7.6 μGy/day (ranging from 1.8 to 219 μGy/day) and the external dose-rate was 13.9 μGy/day (ranging from 6.7 to 35.1 μGy/day). We performed multiple regression analyses to estimate the dose-rate effects on haematological values in peripheral blood and bone marrow. The white blood cell and platelet counts showed an inverse correlation with the internal dose-rate in mature macaques. Furthermore, the myeloid cell, megakaryocyte, and haematopoietic cell counts were inversely correlated and the occupancy of adipose tissue was positively correlated with internal dose-rate in femoral bone marrow of mature macaques. These relationships suggest that persistent whole body exposure to low-dose-rate radiation affects haematopoiesis in Japanese macaques.